2016
DOI: 10.1172/jci85856
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-drug conjugate targeting CD46 eliminates multiple myeloma cells

Abstract: Multiple myeloma is incurable by standard approaches because of inevitable relapse and development of treatment resistance in all patients. In our prior work, we identified a panel of macropinocytosing human monoclonal antibodies against CD46, a negative regulator of the innate immune system, and constructed antibody-drug conjugates (ADCs). In this report, we show that an anti-CD46 ADC (CD46-ADC) potently inhibited proliferation in myeloma cell lines with little effect on normal cells. CD46-ADC also potently e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
95
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 60 publications
(96 reference statements)
1
95
0
1
Order By: Relevance
“…Saporin is a very stable cytotoxic drug that functions by preventing protein synthesis in the cell. It has been used to induce apoptosis of tumour cells in cancer therapies . The potential off‐target effect of ADC treatment was a concern, as splenic CD11c + CD11b + cells expressed the second highest level of CX 3 CR1, but we found that the activated T cells in the spleen and the levels of circulating antibodies including anti‐dsDNA antibodies were not different between ADC‐ and PBS‐treated groups.…”
Section: Discussionmentioning
confidence: 60%
“…Saporin is a very stable cytotoxic drug that functions by preventing protein synthesis in the cell. It has been used to induce apoptosis of tumour cells in cancer therapies . The potential off‐target effect of ADC treatment was a concern, as splenic CD11c + CD11b + cells expressed the second highest level of CX 3 CR1, but we found that the activated T cells in the spleen and the levels of circulating antibodies including anti‐dsDNA antibodies were not different between ADC‐ and PBS‐treated groups.…”
Section: Discussionmentioning
confidence: 60%
“…In addition to recurrent IGH SVs, multiple SVs were detected involving the IGH locus and non-canonical candidate partner genes (selected based on proximity to the translocation breakpoint) including the following: CD46 , which has a role in innate immune recognition23 and has been demonstrated to have increased expression in myeloma cell lines and primary myeloma cells particularly in association with 1q copy number gains 24

TXNDC5 , which has recently been described as a rare but recurrent translocation in myeloma and in this study was detected in a patient with a high hyperdiploid karyotype consistent with a previous report 5

…”
Section: Discussionmentioning
confidence: 99%
“…CD46 , which has a role in innate immune recognition23 and has been demonstrated to have increased expression in myeloma cell lines and primary myeloma cells particularly in association with 1q copy number gains 24…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical in vitro and in vivo studies in mouse xenograft models suggest that SGN-CD325A could prove to be a viable option for treating multiple myeloma in clinical trials 73 . Antibody-drug conjugates for treating multiple myeloma have also been recently developed targeting B-cell maturation antigen (BCMA) with monomethyl auristatin F (MMAF)(GSK2857916) 74 , CD46 with MMAF 75 , and CD56 with the maytansinoid DM1 76 . While the anti-CD56 ADC, lorvotuzumab mertansine, has moved onto clinical trials (NCT00991562), the specificity towards CD46 (CD46-ADC) is the most novel myeloma antibody-drug conjugate developed recently.…”
Section: Engineered Antibodies Enzymes and Antibody-drug Conjugamentioning
confidence: 99%
“…This approach is notable because of the previously underappreciated targeting of CD46. Although, CD46 is not a surface marker required, by myeloma cells or other B-cell lineage cells, it has been shown to be upregulated in myeloma cells because of the copy number duplications on chromosome 1q, but remains unexpressed outside placenta and prostate tissues 75 . Chromosome 1q amplifications are a known marker for poor prognosis in multiple myeloma 75 , so targeting this subset of myeloma is a relatively untapped niche of myeloma research and should, therefore, be developed further.…”
Section: Engineered Antibodies Enzymes and Antibody-drug Conjugamentioning
confidence: 99%